1995
DOI: 10.2307/2291506
|View full text |Cite
|
Sign up to set email alerts
|

Are People Bayesian? Uncovering Behavioral Strategies

Abstract: Economists and psychologists have recently been developing new theories of decision making under uncertainty that can accommodate the observed violations of standard statistical decision theoretic axioms by experimental subjects. We propose a procedure which finds a collection of decision rules that best explain the behavior of experimental subjects. The procedure is a combination of maximum likelihood estimation of the rules together with an implicit classification of subjects to the various rules, and a pena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 14 publications
4
101
0
Order By: Relevance
“…Mixture models are also virtually identical to "latent class models" used in many areas of statistics, marketing and econometrics, even though the applications often make them seem quite different (e.g., Goodman 1974aGoodman , 1974bVermunt and Magidson 2003). In experimental economics, El-Gamal and Grether (1995) estimate a finite mixture model of Bayesian updating behavior, and contrast it to a related approach in which individual subject behavior is classified completely as one type of the other. Stahl and Wilson (1995) develop a finite mixture model to explain behavior in a normal form game, differentiating between five types of boundedly rational players.…”
Section: Weddings Funerals and Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mixture models are also virtually identical to "latent class models" used in many areas of statistics, marketing and econometrics, even though the applications often make them seem quite different (e.g., Goodman 1974aGoodman , 1974bVermunt and Magidson 2003). In experimental economics, El-Gamal and Grether (1995) estimate a finite mixture model of Bayesian updating behavior, and contrast it to a related approach in which individual subject behavior is classified completely as one type of the other. Stahl and Wilson (1995) develop a finite mixture model to explain behavior in a normal form game, differentiating between five types of boundedly rational players.…”
Section: Weddings Funerals and Heterogeneitymentioning
confidence: 99%
“…One could alternatively define a grand likelihood in which observations or subjects are classified as following one model or the other on the basis of the latent probabilities π EUT and π PT . El-Gamal andGrether (1995) illustrate this approach in the context of identifying behavioral strategies in Bayesian updating experiments.…”
mentioning
confidence: 99%
“…Furthermore, some subjects might use one rule, while others use a different one (El Gamal and Grether, 1995). Grether (1992) also argues that subjects may change rules depending on the decision situation (e.g.…”
Section: Number Of Red Chips Predictedmentioning
confidence: 99%
“…1 We begin by interpreting predictions with an ordered probit statistical model assuming strict rationality, but are unable to recover the induced probability. In the spirit of El Gamal and Grether (1995), we then use a mixture type of ordered probit that assumes subjects are bounded rational and heterogeneous-subjects use one of four decision rules to make their predictions or just choose randomly. The first rule assumes strict rationality, while the others are heuristic rules of thumb based on the expected outcome.…”
mentioning
confidence: 99%
“…8 Finally, we note that that our estimation procedure does not actually impose that consumers update in a strict Bayesian manner. El-Gamal and Grether (1995), in their experiment on Bayesian learning, found that, while Bayes' rule was the most commonly used rule, subjects often used a "representativeness heuristic." This means they update too much when they receive new information.…”
Section: Consumer Learning About Qualitymentioning
confidence: 99%